A FAPbI3 perovskite film and a method for preparing an efficient perovskite solar cell

By adjusting the mass ratio of ammonium acetate in the FAPbI3 perovskite precursor solution, a one-step process is achieved to prepare a high-efficiency pure-phase formidinyl perovskite film, which solves the problem of phase change of materials at low temperatures, and improves the efficiency of solar cells and the simplicity of preparation.

CN114678472BActive Publication Date: 2025-05-02NANJING TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210284744.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-22
Publication Date
2025-05-02
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

FAPbI3 perovskite is very easy to convert from α phase to δ phase when it is below 150°C, and it is difficult to prepare uniform and dense films and devices in one-step.

Method used

By regulating the mass ratio of the additive ammonium acetate in the precursor solution, a one-step process is achieved to prepare high-efficiency pure phase formidinyl perovskite film and its perovskite solar cells.

Benefits of technology

A uniform and dense FAPbI3 perovskite film was successfully prepared, which maintained the optical activity of the material, improved the energy conversion efficiency of perovskite solar cells, and simplified the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114678472B_ABST
    Figure CN114678472B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing FAPbI3 perovskite thin films and high-efficiency perovskite solar cells, belonging to the field of optoelectronic materials and devices. In this invention, the preparation of pure-phase FAPbI3 thin films uses a one-step method. Ammonium acetate is used as an additive and dissolved with perovskite components in N,N-dimethylformamide as a precursor solution, which is spin-coated on an FTO conductive substrate already having an electron transport layer. After annealing, a uniform and dense perovskite thin film is prepared. The whole process is carried out in an anhydrous and oxygen-free glove box. Subsequently, post-treatment is carried out on the thin film, and Spiro-OMeTAD is used as a hole transport layer. Then, a MoO3 modification layer and a metal electrode are deposited by vacuum evaporation technology to complete the preparation of the device. The pure-phase FAPbI3 perovskite solar cells prepared by this method have excellent photoelectric conversion efficiency, and in this invention, the use of ammonium acetate as an additive enables the one-step preparation of pure-phase formamidinium perovskite solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a pure-phase FAPbI3 perovskite film and a high-efficiency perovskite solar cell in one step by adjusting the mass of ammonium acetate based on ammonium acetate as a precursor solution additive, in particular to a method for preparing a high-efficiency pure-phase formamidine-based perovskite film in one step by utilizing the additive, and belongs to the field of optoelectronic materials and technology. Background Art

[0002] With the continuous development of society, the environmental problems caused by traditional fossil energy have attracted more and more attention, and the development of clean energy is imminent. With the increasing demand for clean energy, solar power generation has received more and more attention. So far, most solar cells are made of silicon because this material is very good at absorbing light. However, the manufacturing cost of silicon panels is very expensive, and the crystalline silicon solar cells need to be sintered at a high temperature of thousands of degrees during the preparation process, which not only wastes a lot of financial and material resources, but also is not conducive to sustainable development strategies.

[0003] New solar cells including perovskite solar cells, dye-sensitized solar cells, organic solar cells and quantum dot solar cells have emerged. Among them, perovskite solar cells have attracted much attention internationally due to their low cost, simple preparation and excellent photoelectric conversion performance. Therefore, compared with the existing mature crystalline silicon solar cell technology, it has great advantages and also brings optimistic prospects for the commercial application of perovskite solar cells. Among perovskite materials, FAPbI3 perovskite (where FA is formamidine) has been proven to be an ideal candidate material for the preparation of efficient and stable perovskite solar cells. However, FAPbI3 will undergo a phase transition from the optically active α phase to the optically inactive δ phase at temperatures below 150°C. Therefore, obtaining highly crystalline, stable and pure α-phase FAPbI3 perovskite films is crucial to the practical and widespread application of perovskite solar cells. Previous studies mainly used MA doping to obtain FAPbI3 perovskite films. + (Methylamine), Cs + , or Br - Plasma is used to obtain pure α-phase FAPbI3 perovskite, but doping these ions will cause the UV-visible light absorption peak of the perovskite material to blue shift, resulting in a wider band gap of this system. Although the open circuit voltage (V OC ), but reduces the short-circuit current density (J SC) The bandgap of FAPbI3 (~1.48V) is the system closest to the ideal bandgap (1.3V - 1.4V) among known perovskite materials. More importantly, these doping strategies will affect the stability of the device to a certain extent. Therefore, it is particularly important to use a reagent or method that can obtain pure α-phase FAPbI3 without changing its bandgap. Summary of the Invention

[0004] The technical problem solved by the present invention is that FAPbI3 perovskite is extremely easy to transform from the optically active α-phase to the optically inactive δ-phase below 150°C, and it is difficult to prepare a uniform and dense FAPbI3 perovskite thin film and its device by a one-step method.

[0005] To solve the above problems, the technical solution proposed by the present invention is: A method for preparing highly efficient pure-phase formamidinium perovskite thin film and its perovskite solar cell by a one-step method by regulating the mass ratio of the additive ammonium acetate (NH4Ac) in the precursor, including the following steps:

[0006] (1) Mix lead iodide and formamidinium iodide in a molar ratio of 1.2:1, and add the additive ammonium acetate in a mass ratio X

[0007] 15% < X < 25%, dissolve it in N,N-dimethylformamide solvent to prepare a new FAPbI3 perovskite precursor solution, and heat and stir to dissolve for 0.5 - 1 hour at a temperature below 50°C;

[0008] (2) Spin-coat and deposit an electron transport material on a cleaned and treated FTO transparent conductive glass sheet;

[0009] (3) In an anhydrous and oxygen-free glove box, spin-coat the prepared perovskite precursor solution on the FTO conductive substrate with an electron transport layer, and anneal at 170°C for 10 minutes to obtain a flat and dense perovskite thin film;

[0010] (4) Spin-coat a mixed solution of formamidinium iodide and chloromethylammonium on the perovskite layer for post-treatment;

[0011] (5) Spin-coat a hole transport layer on the perovskite layer;

[0012] (6) Vacuum deposit an interface modification layer and a metal electrode on the hole transport layer;

[0013] The post-treatment layer spin-coated and deposited in step (4) is formamidinium iodide FAI and chloromethylammonium FACl; the specific steps are as follows:

[0014] (a) Dissolve 10mg of formamidinium iodide and 5mg of chloromethylammonium in 1mL of isopropyl

[0015] Alcohol (IPA) solution;

[0016] (b) Mix the prepared FACl and FAI IPA solution at room temperature and transfer

[0017] Stir at 300 rpm for 3 hours;

[0018] (c) Take 40 uL of the solution obtained in step (2) and spin-coat it on the perovskite at 4000 rpm for 30 s.

[0019] Preferably, the mass ratio of the additive ammonium acetate to the perovskite precursor materials lead iodide and formamidine iodide is 20%.

[0020] Preferably, in the step (2), the electron transport layer on the transparent conductive FTO glass is SnO2, and the specific steps are as follows:

[0021] (1) Spin coating conditions: 4000 rpm for 30 seconds.

[0022] (2) After spin coating, anneal at 150°C for 30 minutes.

[0023] Preferably, the film preparation in step (3) is performed by spin coating and annealing in a water-free and oxygen-free glove box, and the specific steps are as follows:

[0024] (1) The spin coating condition is 4000 rpm for 30 seconds.

[0025] (2) After spin coating, annealing is performed on a hot plate at 170°C for 10 minutes.

[0026] Preferably, the hole transport layer deposited by spin coating in step (5) is Spiro-OMeTAD; the specific steps are as follows:

[0027] (1) Dissolve 73.2 mg of Spiro-OMeTAD in 1 mL of chlorobenzene;

[0028] (2) 520 mg of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 mL of acetonitrile solution.

[0029] (3) Add 28.8 μL of TBP solution to the Spiro-OMeTAD solution;

[0030] (4) Add 17.6 μL of lithium salt solution to the Spiro-OMeTAD solution;

[0031] (5) stirring the mixed solution at room temperature for 2 hours;

[0032] (6) The spin coating condition is 3000 rpm for 30 s.

[0033] Preferably, in step (6), the interface modification layer is MoO3 and the metal electrode is Ag. The specific steps are:

[0034] (1) MoO3 is evaporated on the hole transport layer with a thickness of 5 nm;

[0035] (2) The thickness of the metal Ag electrode is 100 nm.

[0036] In order to solve the above problems, another technical solution proposed by the present invention is: a one-step method for preparing high-efficiency pure phase formamidinium-based perovskite films and perovskite solar cells thereof by regulating the mass ratio of the additive ammonium acetate (NH4Ac) in the precursor solution.

[0037] In order to solve the above problems, another technical solution proposed by the present invention is: the one-step preparation of high-efficiency pure phase formamidinium-based perovskite film and its perovskite solar cell is achieved by regulating the mass ratio of the additive ammonium acetate (NH4Ac) in the precursor solution, and the application of the prepared perovskite solar cell in the optoelectronic field.

[0038] Beneficial effects of the present invention:

[0039] (1) Previous studies mainly used MA doping + (methylamine ion), Cs + Or Br - Plasma is used to obtain pure α-phase FAPbI3 perovskite, but doping these ions will cause the ultraviolet-visible light absorption peak of the perovskite material to blue-shift, resulting in a wider band gap of the system. Although the open circuit voltage (V OC ), but reduces the short-circuit current density (J SC ), and the band gap of FAPbI3 (~1.48V) is the system closest to the ideal band gap (1.3V-1.4V) among the known perovskite materials. However, the pure phase formamidinium-based perovskite solar cell prepared by the present invention uses ammonium acetate as an additive to obtain a uniform and dense perovskite film without affecting the band gap, thereby being able to prepare a pure phase FAPbI3 perovskite solar cell with excellent energy conversion efficiency.

[0040] (2) The current methods for preparing formamidite-based perovskite solar cells mainly include the antisolvent method and the two-step method. The antisolvent method requires the use of a solvent with a low saturated vapor pressure, which is prone to produce a large amount of harmful gases and requires high precision in operation, while the two-step method is relatively cumbersome. However, the present invention adopts a one-step method to prepare high-efficiency pure-phase formamidite-based FAPbI3 perovskite solar cells, which is simple to operate and is conducive to its industrialization.

[0041] (3) By adjusting the amount of additives and subsequent treatment, a uniform and dense FAPbI3 perovskite film can be prepared. The present invention determines that the amount of additives is 15%-25% of the mass of the precursor material. A mass ratio of less than 15% has little improvement on the crystallinity of the film, and a mass ratio of more than 25% is difficult to dissolve.

[0042] (4) The post-treatment of the perovskite film with the isopropanol solution of iodoformamidine and chloroformamidine used in the present invention can effectively convert the uncoordinated lead iodide into optically active formamidine-based perovskite, which can effectively improve the energy conversion efficiency of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The present invention will be further described below in conjunction with the accompanying drawings.

[0044] Figure 1 is a UV-vis absorption spectrum of a pure phase FAPbI3 film prepared using ammonium acetate as an additive in Example 2 of the present invention;

[0045] Figure 2 The XRD diagrams of the pure phase FAPbI3 film prepared by using ammonium acetate as an additive in Example 2 of the present invention and the film without post-treatment in Comparative Example 3;

[0046] Figure 3 is a SEM image of a pure phase FAPbI3 film prepared using ammonium acetate as an additive in Example 2 of the present invention;

[0047] Figure 4 is a SEM image of the additive-free perovskite film in Comparative Example 4;

[0048] Figure 5 This is a device structure diagram of a pure-phase FAPbI3 perovskite solar cell prepared using ammonium acetate as an additive in Example 2 of the present invention;

[0049] Figure 6 The JV curves of the ammonium acetate perovskite solar cells added with 15%, 20%, and 25% by mass in Example 1, Example 2, and Example 3 of the present invention, respectively; DETAILED DESCRIPTION

[0050] Example 1

[0051] This embodiment uses ammonium acetate as an additive to the FAPbI3 perovskite precursor solution to prepare a pure phase FAPbI3 perovskite film with low defect state density and large grain size and a perovskite solar cell thereof by adjusting the amount of ammonium acetate added. For a full understanding, the laboratory humidity condition of the present invention is greater than 70%. It mainly includes the following steps:

[0052] Step 1) The etched FTO conductive glass was ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 15 minutes each, dried with nitrogen, and then dried in an oven at 100° C. for 30 minutes to obtain a clean FTO substrate.

[0053] Step 2) 662.4 mg of lead iodide, 206.6 mg of iodine formamidine and 130.4 mg of an ammonium acetate additive having a mass ratio of 15% are weighed in a ratio of 1.2:1, dissolved in 1 mL of N,N-dimethylformamide (DMF) solvent, and stirred at 48 ° C for 1 hour until completely dissolved to prepare a perovskite precursor solution.

[0054] Step 3) 73.2 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene; 520 mg of lithium bis(trifluoromethanesulfonate)imide was dissolved in 1 mL of acetonitrile solution; 28.8 μL of TBP solution was added to the Spiro-OMeTAD solution, and 17.6 μL of lithium salt solution was added to the Spiro-OMeTAD solution; the mixed solution was stirred at room temperature for 2 hours; the spin coating condition was 3000 rpm for 30 seconds;

[0055] Step 4) dissolving 10 mg of iodoformamidine and 5 mg of chloroformamidine in 1 mL of isopropanol solution;

[0056] The solution was stirred at 300 rpm for 3 h at room temperature; the spin coating condition was 3000 rpm for 30 s;

[0057] Step 5) The FTO substrate cleaned in step 1) is treated with ultraviolet ozone for 15 minutes.

[0058] Step 6) Take 40 μL of electron transport material SnO2 and drop it onto the FTO substrate treated in step 4), and use a coating machine to spin coat it into a film at a speed of 4000 rpm for 30 seconds, and then anneal the FTO spin-coated with SnO2 at 150°C for 30 minutes.

[0059] Step 7) Take 100 μL of the perovskite precursor solution prepared in step 2) and drop it onto the FTO substrate in step 6), spin-coat it into a film, and then anneal it to form a perovskite film. The spin-coating speed of the perovskite precursor solution is 4000 rpm for 30 seconds, and anneal it at 170° C. for 10 minutes in a water-free and oxygen-free glove box.

[0060] Step 8) Spin-coating the iodoformamidine and formamidine chloride post-treatment materials of step 4) onto the perovskite film of step 7), and the spin-coating of the iodoformamidine and formamidine chloride post-treatment materials is performed at 3000 rpm for 30 seconds.

[0061] Step 9) Spin-coat the hole transport material of step 3) onto the perovskite film treated with iodoformamidine and chlorinated formamidine in step 8), and spin-coat Spiro-OMeTAD at 3000 rpm for 30 seconds to form a hole transport layer.

[0062] Step 10) Vacuum evaporation technology is used to evaporate 5nm MoO3 on the hole transport layer of step 9), and then 100nm metal electrode Ag is evaporated to obtain a perovskite solar cell.

[0063] Step 11) Under standard test conditions (AM1.5G illumination), the energy conversion efficiency of the optimal battery device prepared in this example is 14.68%, the open circuit voltage is 1.01V, and the short circuit current is 23.35mA / cm 2 , the filling factor is 61.97%;

[0064] Example 2

[0065] This embodiment uses ammonium acetate as an additive to the FAPbI3 perovskite precursor solution to prepare a pure phase FAPbI3 perovskite film with low defect state density and large grain size and a perovskite solar cell thereof by adjusting the amount of ammonium acetate added. For a full understanding, the laboratory humidity condition of the present invention is greater than 70%. It mainly includes the following steps:

[0066] Step 1) The etched FTO conductive glass was ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 15 minutes each, dried with nitrogen, and then dried in an oven at 100° C. for 30 minutes to obtain a clean FTO substrate.

[0067] Step 2) 662.4 mg of lead iodide, 206.6 mg of iodine formamidine and 173.8 mg of an ammonium acetate additive having a mass ratio of 20% are weighed in a ratio of 1.2:1, dissolved in 1 mL of N,N-dimethylformamide (DMF) solvent, and stirred at a temperature below 50°C for 1 hour until completely dissolved to prepare a perovskite precursor solution.

[0068] Step 3) 73.2 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene; 520 mg of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 mL of acetonitrile solution; 28.8 μL of TBP solution was added to the Spiro-OMeTAD solution, and 17.6 μL of lithium salt solution was added to the Spiro-OMeTAD solution;

[0069] The mixed solution was stirred at room temperature for 2 hours; the spin coating condition was 3000 rpm for 30 seconds;

[0070] Step 4) dissolving 10 mg of iodoformamidine and 5 mg of chloroformamidine in 1 mL of isopropanol solution;

[0071] The solution was stirred at 300 rpm for 3 h at room temperature; the spin coating condition was 3000 rpm for 30 s;

[0072] Step 5) The FTO substrate cleaned in step 1) is treated with ultraviolet ozone for 15 minutes.

[0073] Step 6) Take 40 μL of electron transport material SnO2 and drop it onto the FTO substrate treated in step 4), and use a coating machine to spin coat it into a film at a speed of 4000 rpm for 30 seconds, and then anneal the FTO spin-coated with SnO2 at 150°C for 30 minutes.

[0074] Step 7) Take 100 μL of the perovskite precursor solution prepared in step 2) and drop it onto the FTO substrate in step 6), spin-coat it into a film, and then anneal it to form a perovskite film. The spin-coating speed of the perovskite precursor solution is 4000 rpm for 30 seconds, and anneal it in a water-free and oxygen-free glove box at 170° C. for 10 minutes.

[0075] Step 8) Spin-coating the iodoformamidine and chloroformamidine post-treatment materials of step 4) onto the perovskite film of step 7), and the spin-coating of the iodoformamidine and chloroformamidine post-treatment materials is performed at 3000 rpm for 30 seconds.

[0076] Step 9) Spin-coat the hole transport material of step 3) onto the perovskite film treated with iodoformamidine and chlorinated formamidine in step 8), and spin-coat Spiro-OMeTAD at 3000 rpm for 30 seconds to form a hole transport layer.

[0077] Step 10) Vacuum evaporation technology is used to evaporate 5nm MoO3 on the hole transport layer of step 9), and then 100nm metal electrode Ag is evaporated to obtain a perovskite solar cell.

[0078] Step 11) Under standard test conditions (AM1.5 G illumination), the optimal battery device prepared in this example has an energy conversion efficiency of 20.49%, an open circuit voltage of 1.06 V, and a short circuit current of 25.56 mA / cm 2 , the filling factor is 74.66%;

[0079] Example 3

[0080] This embodiment uses ammonium acetate as an additive to the FAPbI3 perovskite precursor solution to prepare a pure phase FAPbI3 perovskite film with low defect state density and large grain size and a perovskite solar cell thereof by adjusting the amount of ammonium acetate added. For a full understanding, the laboratory humidity condition of the present invention is greater than 70%. It mainly includes the following steps:

[0081] Step 1) The etched FTO conductive glass was ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 15 minutes each, dried with nitrogen, and then dried in an oven at 100° C. for 30 minutes to obtain a clean FTO substrate.

[0082] Step 2) 662.4 mg of lead iodide, 206.6 mg of iodine formamidine and 25% by mass of ammonium acetate additive, i.e. 217.3 mg, were weighed in a ratio of 1.2:1, dissolved in 1 mL of N, N-dimethylformamide (DMF) solvent, and stirred at a temperature below 50° C. for 1 hour until completely dissolved to prepare a perovskite precursor solution.

[0083] Step 3) 73.2 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene; 520 mg of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 mL of acetonitrile solution; 28.8 μL of TBP solution was added to the Spiro-OMeTAD solution, and 17.6 μL of lithium salt solution was added to the Spiro-OMeTAD solution;

[0084] The mixed solution was stirred at room temperature for 2 hours; the spin coating condition was 3000 rpm for 30 seconds;

[0085] Step 4) dissolving 10 mg of iodoformamidine and 5 mg of chloride formamidine in 1 mL of isopropanol solution;

[0086] The solution was stirred at 300 rpm for 3 h at room temperature; the spin coating condition was 3000 rpm for 30 s;

[0087] Step 5) The FTO substrate cleaned in step 1) is treated with ultraviolet ozone for 15 minutes.

[0088] Step 6) Take 40 μL of electron transport material SnO2 and drop it onto the FTO substrate treated in step 4), and use a coating machine to spin coat it into a film at a speed of 4000 rpm for 30 seconds, and then anneal the FTO spin-coated with SnO2 at 150°C for 30 minutes.

[0089] Step 7) Take 100 μL of the perovskite precursor solution prepared in step 2) and drop it onto the FTO substrate in step 6), spin-coat it into a film, and then anneal it to form a perovskite film. The spin-coating speed of the perovskite precursor solution is 4000 rpm for 30 seconds, and anneal it at 170° C. for 10 minutes in a water-free and oxygen-free glove box.

[0090] Step 8) Spin-coating the iodoformamidine and chloroformamidine post-treatment materials of step 4) onto the perovskite film of step 7), and the spin-coating of the iodoformamidine and chloroformamidine post-treatment materials is performed at 3000 rpm for 30 seconds.

[0091] Step 9) Spin-coat the hole transport material of step 3) onto the perovskite film treated with iodoformamidine and chloroformamidine in step 8), and spin-coat Spiro-OMeTAD at 3000 rpm for 30 seconds to form a hole transport layer.

[0092] Step 10) Vacuum evaporation technology is used to evaporate 5nm MoO3 on the hole transport layer of step 9), and then 100nm metal electrode Ag is evaporated to obtain a perovskite solar cell.

[0093] Step 11) Under standard test conditions (AM1.5 G illumination), the energy conversion efficiency of the optimal battery device prepared in this example is 17.04%, the open circuit voltage is 1.04V, and the short circuit current is 24.22mA / cm 2 , the filling factor is 67.35%;

[0094] Comparative Example 1

[0095] The use of other additives, such as ammonium chloride (NH4Cl), methylamine acetate (MAAc) and hydroxylamine acetate (HAAc), cannot produce uniform and dense films, and the energy conversion efficiency of the prepared perovskite solar cells is low.

[0096] Comparative Example 2

[0097] Although the guanidine-based perovskite film prepared using ammonium acetate at a mass ratio of 10% has some improvement compared to the one without additives, the overall quality of the film is still poor, and the energy conversion efficiency of the prepared perovskite solar cell is only 7.07%. When the mass ratio is greater than 25%, the additive is difficult to dissolve in the precursor solution, making it impossible to prepare the device.

[0098] Comparative Example 3

[0099] If the film is not treated with a mixed isopropanol solution of iodoformamidine and chloroformamidine, it contains more uncoordinated lead iodide (such as attached Figure 2 ), the excess lead iodide that is not optically active will affect the performance of the device. If the device prepared with the optimal additive mass ratio is not post-processed, the energy conversion efficiency is only 15.91%.

[0100] Comparative Example 4

[0101] The one-step method for preparing pure phase formamidite-based perovskite solar cells without adding ammonium acetate additives, according to the molar ratio of lead iodide to iodoformamidite of 1.2:1, the prepared film has a small grain size and many holes, and the energy conversion efficiency of the device prepared by this method is only 3.89%. Compared with the preparation method of the present invention using ammonium acetate as an additive, due to the auxiliary crystallization effect of ammonium acetate, a film with a larger grain size and uniformity without holes can be prepared, and the prepared perovskite solar cell has excellent energy conversion efficiency (such as the addition of Figure 3 and attached Figure 5 )

[0102] In general, the present invention uses ammonium acetate additive as the solvent of the pure-phase FAPbI3 perovskite precursor solution and adjusts the mass ratio of the additive in the precursor solution to enable it to play an auxiliary crystallization role to prepare high-efficiency FAPbI3 perovskite film and solar cell. The prepared perovskite film has a grain size of micron level and a dense and smooth morphology, and the prepared perovskite device has excellent device efficiency. The pure-phase FAPbI3 perovskite solar cell prepared by this method is simple to operate, has a high photoelectric conversion efficiency, and has a rare industrialization advantage.

[0103] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.

Claims

1. A method for preparing a FAPbI3 perovskite solar cell, characterized in that: It includes the following steps: (1) Lead iodide and formamidinium iodide are mixed at a molar ratio of 1.2:1, and ammonium acetate as an additive is added at a mass ratio X to the perovskite precursor materials lead iodide and formamidinium iodide, where 15% < X < 25%. They are dissolved in N,N-dimethylformamide solvent to prepare a new FAPbI3 perovskite precursor solution, and heated and stirred for dissolution at a temperature below 50 °C for 0.5 - 1 hour; (2) Spin-coat and deposit an electron transport material on the cleaned and treated FTO transparent conductive glass sheet; (3) Spin-coat the prepared perovskite precursor solution on the FTO conductive substrate with an electron transport layer in an anhydrous and oxygen-free glove box, and anneal at 170 °C for 10 minutes to obtain a flat and dense perovskite thin film; (4) Spin-coat a mixed solution of formamidinium iodide and chloromethylammonium iodide on the perovskite layer for post-treatment; (5) Spin-coat a hole transport layer on the perovskite layer; (6) Vacuum deposit an interface modification layer and a metal electrode on the hole transport layer; In the step (4), the spin-coated post-treatment layer is formamidinium iodide FAI and chloromethylammonium iodide FACl; the specific steps are as follows: (a) Dissolve 10 mg of formamidinium iodide and 5 mg of chloromethylammonium iodide in 1 mL of isopropanol solution; (b) Stir the prepared mixed IPA solution of FACl and FAI at room temperature at a rotation speed of 300 rpm for 3 hours; (c) Take 40 μL of the solution obtained in step (b) and spin-coat it on the perovskite, and the spin-coating conditions are 4000 revolutions for 30 s.

2. The method for preparing a FAPbI3 perovskite solar cell according to claim 1, characterized in that: The additive ammonium acetate is at a mass ratio of 20% to the perovskite precursor materials lead iodide and formamidinium iodide.

3. The method for preparing a FAPbI3 perovskite solar cell according to claim 1, characterized in that: In the step (2), the electron transport layer on the transparent conductive FTO glass is SnO2, and the specific steps are as follows: The spin-coating conditions are 4000 revolutions for spin-coating for 30 seconds, After spin-coating, anneal at 150 °C for 30 minutes.

4. The method for preparing a FAPbI3 perovskite solar cell according to claim 1, characterized in that: In the step (3), the thin film preparation is carried out by spin-coating and annealing in an anhydrous and oxygen-free glove box, and the specific steps are as follows: The spin-coating conditions are 4000 revolutions for spin-coating for 30 seconds; After spin-coating, anneal on a hot stage, and the conditions are 170 °C for 10 minutes.

5. The method for preparing a FAPbI3 perovskite solar cell according to claim 1, characterized in that: In the step (5), the spin-coated hole transport layer is Spiro-OMeTAD; the specific steps are as follows: (1) Dissolve 73.2 mg of Spiro-OMeTAD in 1 mL of chlorobenzene; (2) Dissolve 520 mg of lithium bis(trifluoromethanesulfonyl)imide in 1 mL of acetonitrile solution; (3) Add 28.8 μL of TBP solution to the Spiro-OMeTAD solution; (4) Add 17.6 μL of the lithium salt solution to the Spiro-OMeTAD solution; (5) Stir the mixed solution at room temperature for 2 hours; (6) The spin-coating conditions are 3000 revolutions for 30 s.

6. The method for preparing a FAPbI3 perovskite solar cell according to claim 1, characterized in that: In the step (6), the interface modification layer is MoO3 and the metal electrode is Ag; the specific steps are: MoO3 is vacuum deposited on the hole transport layer with a thickness of 5 nm; The thickness of the metal Ag electrode is 100 nm.

7. An FAPbI3 perovskite solar cell prepared by the method according to any one of claims 1 - 6.

8. Application of the FAPbI3 perovskite solar cell according to claim 7 in the field of optoelectronics.

Citation Information

Patent Citations

  • A preparation method of perovskite solar cell

    CN109065727A

  • Efficient and stable perovskite solar cell based on novel ionic liquid methylamine formate as well as preparation method and application of perovskite solar cell

    CN111952456A